Phenothiazinen-Dimesitylarylborane-Based Thermally Activated Delayed Fluorescence: High-Performance Non-doped OLEDs With Reduced Efficiency Roll-Off at High Luminescence - Tang, Xiangyang; Tao, Yanchun; Liu, Hui; Liu, Futong; He, Xin; Peng, Qiming; Li, Jinyu; Lu, Ping (Frontiers in Chemistry, 2019)
We report a phenothiazinen-dimesitylarylborane thermally activated delayed fluorescence molecule that exhibits high external quantum efficiency (EQE) in nondoped organic light emitting diodes (OLEDs) at high luminescence. The nondoped device shows green electroluminescence with an emission peak of 540 nm and a maximum EQE of 19.66% obtained at a luminescence of ~ 170 cd m-2. The EQE is still as high as 17.31% at high luminescence of 1500 cd m-2 with small efficiency roll-off.